Design and Experimental Analysis of an Air-Suction Wheat Precision Hill-Seed Metering Device - Ziheng Fang; Jing Zhang; Jincheng Chen; Feng Pan; Baiwei Wang; Chao Ji (Agriculture)
The uniformity of the wheat distribution within and between rows has a significant effect on crop population structure, leading to decreased yield as nonuniformity increases. Traditional drills are influenced by soil porosity and flatness in the field, making accurate control of sowing depth and amount challenging and resulting in an uneven spatial distribution of gramineous seedlings. Precision cave-sowing technology effectively enhances wheat population distribution uniformity. However, owing to limitations in existing mechanical precision cave planters, their operational speed is lower than that of drill planters. To address these issues, this study designed an air-suction precision wheat seed dispenser, described its basic structure and working principle, and developed a seed mechanical model. A theoretical analysis was conducted on the working process and key components of the seed feeder. A suitable mould hole diameter was determined to be 1.6~2.0 mm, and the rotation speed range for the seed plate was found to be 65~85 r·min−1. Fluent simulations were used to determine the influence of orifice type on gas chamber flow fields; DEM-CFD-coupled simulation identified an appropriate negative pressure range of 2.6~3.4 kPa for optimal performance during seeding operations. Orthogonal experiments were carried out with mould hole diameter, negative pressure size, and seed plate speed as test factors alongside a qualification index, multiple sowing index, and missed sowing index as response indicators—leading to regression equation establishment, which yielded the optimal parameter combination: mould hole diameter at 1.8 mm; gas chamber negative pressure at 3.2 kPa; and a seed plate speed of 74 r·min−1, with the corresponding forwards speed of the machine being 7 km·h−1—resulting in a qualification index of 91.66%, multiple sowing index of 5.98%, and missed sowing index of 2.36%. This pneumatic suction type wheat precision seeder achieves equivalent operational speeds as traditional drills while enabling precision seeding.